Foundations of national identity : from Catalonia to Europe - Llobera, Josep R. (New directions in anthropology, 2004)
What we are experiencing is an increasing autonomy of ethnonations, i.e. nations without a state, in the wake of a weakening of the multinational states and the transfer of their sovereignty upwards, in the case of Europe to the federation of the European Union, and downwards to the "ethnonations"."--Jacket